Exploration of sustainable attitudes and behaviors and the role of planned behavior amongst the AUC Community - Khairy, Natalie Tamer (AUC Knowledge Fountain, 2024)
This thesis explores the use of a new Framework that was developed by combining both the Theory of Planned Behavior (TPB) and Knowledge, Attitudes, and Practices (KAP) theory to study the sustainability behaviors of students, faculty, and staff at the American University in Cairo (AUC). The research aims to provide insights into the factors influencing sustainable behaviors and how these factors differ across the three groups. The study used a combination of questions from the sustainability awareness questionnaire (SAQ) and Sulitest that was customized to the cultural context of the target group. The survey was administered to a sample of students, faculty, and staff at the AUC. The data collected was analyzed using SPSS to create both linear and multiple regression models to understand the impact of the independent variables on the dependent variables. The results of the study indicated that both extended TPB and the new framework were useful in understanding sustainable behaviors but that they provide different insights. The results also suggest that the factors that influence sustainable behaviors are complex, and that they vary across different groups. While perceived behavioral control and attitudes were found to be important factors for all groups, knowledge and awareness were more important for staff than for students or faculty. The study has several implications for sustainable behavior interventions; it suggests that using the newly proposed conceptual framework helped in better understanding the factors impacting behavior. Furthermore, it highlights the importance of addressing knowledge and awareness gaps, particularly for staff. Overall, it highlights the need to address the broader social and cultural context in which sustainable behaviors occur, and it contributes to the overall understanding of researchers of sustainable behaviors for designing effective interventions to promote sustainability in higher educational institutes.